Taxonomic review of the genera Micridium Motschulsky, 1869 and Micridina Johnson, 1969 (Coleoptera: Ptiliidae) with eleven new species including the first records from South America and Madagascar - Darby, Michael (Zootaxa, 2017)
The six recognised species of the genus Micridium Motschulsky, 1869: M. vittatum (Motschulsky, 1845) M. halidaii (Matthews, 1868), M. angulicolle (Fairmaire, 1858), M. lineatum (Le Conte, 1863). M. rhodeanum (Casey, 1924) and M. groehni Polilov & Perkovsky, 2004 are reviewed and eleven new species: M. attenboroughi sp.n., M. boliviense sp.n., M. elegans sp. n., M. foveatum sp.n., M. inornatum sp.n., M. johnsoni sp.n., M. newtoni sp.n., M. oweni sp.n., M. proprium sp.n., M. quadridens sp.n. and M. thayerae sp.n. are added. The new species are the first records of the genus from South America and Madagascar. The morphological characteristics separating Micridium from other genera in the tribe Ptiliini are discussed and the genus synonymised with the closely related monotypic genus Micridina Johnson, 1969 with its single species M. hilli Johnson, 1969. The synonymy of Dilinium Casey, 1924 with Micridium is confirmed and the type species D. rhodeanum Casey, 1924 re-described. Micridium groehni, described from a single specimen in Baltic amber, does not appear to belong to Micridium as defined here. A key to the new species is provided.